Kajian Keputusan Konsumen Lokal Dalam Pembelian Produk Elektronik Ramah Lingkungan - Eka Khrisnayodi, Benedict Lanzio (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
With the increasing income and education in the society,the tendencies to choose consuming green (environmentallyfriendly) products are increasing too. The usages of greenproducts are also influenced by the product information. Thepopularity of the brand for the green products is also aninfluencing factor in the buying decision of the consumer.Consumer can see that the making of green products surelyrequire professionalism and brand trust. The awareness level forthe preservation of the environment has impact on the buyingdecision of green products. This is mostly influenced by the easyaccess of information about green products, which is turn canincrease the awareness of the need for environmental friendliness.Keywords: green products, buying decision, environmentalfriendliness, consumer